Effect of kisspeptin on calcium signalling in cultured rHypoE-8 cell line - Kutlu, Selim; Ozdemir, Gokcen; Sahin, Zafer; Ozcan, Mete; Canpolat, Sinan; Kelestimur, Haluk (Wiley-Blackwell, 2015)
[Abstract Not Available]